New taxa of Aboilinae (Insecta, Orthoptera, Prophalangopsidae) from the Middle Jurassic of Daohugou, Inner Mongolia, China - Fang, Yan; Zhang, Haichun; Wang, Bo; Zhang, Yutao (Zootaxa, 2007)
A new genus, Sigmaboilus gen. nov., is established and attributed to Aboilinae (Insecta, Orthoptera, Prophalangopsidae). It includes three new species, Sigmaboilus gorochovi sp. nov., S. sinensis sp. nov., and S. longus sp. nov., from the Middle Jurassic of Daohugou in Inner Mongolia, China, and is distinguished from other genera within Aboilinae by the remarkably long C vein in the tegmen.